Corn (Zea mays L) Development Based on Drone-Based Vegetation Index Trough NPK Fertilization - Padjung, Rusnadi; BDR, Muh. Farid; Adzima, Ahmad Fauzan; Saleh, Ifayanti Ridwan; Musa, Yunus; Nasaruddin, N.; Anshori, Muhammad Fuad; Muharram, Nur Qalbi Zaesar; Amier, Nirwansyah (Universitas Sembilanbelas November Kolaka, 2023)
Maize is one of the most important food crops after rice. This study aimed to obtain one or more doses of fertilizers that provide high growth and productivity, obtain one or more varieties of maize that have increased productivity, and obtain interactions between doses of fertilizers with maize varieties that deliver high growth and productivity. The research was conducted at the Experimental Farm (KP) of the Bajeng Cereal Crops Research Center, Bajeng District, Gowa Regency, South Sulawesi. At an altitude of 27.2 meters above sea level, with coordinates 5018'21.5